Diseño de prototipo electrónico para terapia física de muñeca afectada por síndrome del túnel del carpo (2020)
This paper describes the process of designing an electronic prototype for physical, passive, wrist therapy affected by Carpo Tunnel Syndrome (STC), the highest frequency occupational disease in our country, and which causes the highest number of temporary and permanent disabilities. The work took place in four major stages: the first, a documentary review of such devices available in the current market, and prototypes and simulations by different researchers; another writing of the proposal in accordance with the above, the next, of construction, observation and computer design of the device, and the last corresponding to the analysis of results and conclusions. With its own funding, the device was first built to better understand the logic of its design, with attention to the therapeutic needs of bending and extension of the wrist and thus, reach the projection by computer. Control and programming of an MG966 servo motor was carried out, using the Arduino program; the device is an Arduino 2560 designed using Autodesk Inventor. The device performs bending and extension movements at 65 degrees, each, which allow the STC-affected wrist to be rehabilitated to release the median nerve.